Azido(η(5)-pentamethylcyclopentadienyl)[2-(pyridin-2-yl)phenyl]iridium(III) - Ariyoshi, Keita (International Union of Crystallography, 2013)
In the title compound, [Ir(C(10)H(15))(C(11)H(8)N)(N(3))], the Ir(III) ion is coordinated by three anionic ligands, namely, pentamethylcyclopentadienyl (Cp*(−)), 2-(pyridin-2-yl)phenyl (ppy(−)) and azide (N(3) (−)), and adopts a three-legged piano-stool geometry The coordination mode of N(3) (−) is typical for Cp*Ir(III)–N(3) complexes, with an Ir—N(N(3)) bond length of 2.125 (2) Å and an Ir—N=N bond angle of 116.5 (2)°. The N(3) (−) ligand is almost linear [N=N=N = 176.0 (3)°], and the N=N bond length between the central and coordinating N atom and that between the central and non-coordinating terminal N atom are 1.194 (3) and 1.157 (3) Å, respectively. For the ppy(−) ligand, the Ir—C and Ir—N bond lengths are 2.066 (3) and 2.079 (3) Å, respectively, which are rather close to each other, compared to the related Ir(III)– or Rh(III)–ppy complexes. The Ir—C(Cp*) bond lengths vary in the range 2.163 (2)–2.232 (2) Å, indicating a strong trans influence of the cyclometallated C-donor atom of the ppy(−) ligand.